Validation of the Zung self-rating depression scale (SDS) in older adults - Jari Jokelainen; Markku Timonen; Sirkka Keinänen-Kiukaanniemi; Pirjo Härkönen; Heidi Jurvelin; Kadri Suija (Taylor & Francis Group, 2019)
Objective: The main objective of this study was to investigate the psychometric properties of the Zung Self-Rating Depression Scale (SDS) and evaluate screening parameters capability of the SDS with the Beck Depression Inventory (BDI-21) among the elderly population. Design: A population-based study Setting: Community Subjects: 520 adults, aged 72-73 years, living in the city of Oulu, Finland. Main outcome measures: The screening parameters of the SDS questions and BDI-21 for detecting severity of depression. The Mini Neuropsychiatric Interview for diagnosing major depression. Results: The optimal cut-off point for the SDS was 39. The sensitivity and specificity parameters for this cut-off point were 79.2% (95% CI 57.8-92.9) and 72.2% (95% CI 67.9-76.1), respectively. Positive and negative predictive values were 12.5% (95% CI 7.7-18.8) and 98.6% (95% CI 96.7-99.5), respectively. Moreover, there was no statistically significant difference in diagnostic accuracy indices of the cut-off points 39 and 40. In a receiver operating characteristic analysis, the area under the curve was 0.85 (95%CI 0.77-0.92) for the SDS total score and 0.89 (95% CI 0.83-0.96) for the BDI-21 (p = 0.137). Conclusion: Using the traditional cut-off point, the SDS was convenient for identifying clinically meaningful depressive symptoms in an elderly Finnish population when compared with the BDI-21 which is one of the most commonly used depression screening scales. The sensitivity and specificity of these two screening tools are comparable. Based on our study, the SDS is convenient for identifying clinically meaningful depressive symptoms among older adults at the community level.Key points The widely used Zung Self-Rating Depression Scale (SDS) has not previously been validated among elderly people at the community level. The sensitivity and specificity of SDS (cut-off point 39) were 79.2% and 72.2%. The positive and negative predictive values for SDS were 12.5% and 98.6%. SDS is convenient for identifying major depression in an elderly population and regarding sensitivity and specificity comparable to BDI-21.